Alpha-clustered hypernuclei and chiral SU(3) dynamics. (1st January 2014) - Hiyama, Emiko; Funaki, Yasuro; Kaiser, Norbert; Weise, Wolfram
Abstract: Selected light hypernuclei are studied using an α cluster model approach (the Hyper-THSR wave function) in combination with a density-dependent Λ hyperon–nuclear interaction derived from chiral SU(3) effective field theory. This interaction includes important two-pion exchange processes involving Σ N intermediate states and associated three-body mechanisms as well as effective mass and surface terms arising in a derivative expansion of the in-medium Λ self-energy. Applications and calculated results are presented and discussed for ^13_Λ C and _Λ ^9 Be. The lightest α clustered hypernucleus, ^5_Λ He, is also discussed in this context.